Cutaneous lymphoma: a retrospective clinico-pathological study during the 1997-2004 Period in Edgardo Rebagliati-Martins Hospital, Essalud, Lima, Peru - Bletrán Gárate, Brady (2018)
Introduction: Clinico-pathological features of malignant lymphomas vary according to geography. The skin is the second site for extranodal Non-Hodgkin Lymphoma. Primary cutaneous lymphoma has a different clinical behavior and prognosis compared with systemic lymphomas.Objective: The aim of this study was to determine the relative rate of cutaneous lymphomas and to examine the clinical relevance of the new WHO/EORTC classification and survival in Peruvian persons with primary cutaneous lymphoma.Methods: We conducted a clinico-pathological retrospective study in 78 cases of cutaneous lymphoma diagnosed between 1997 and 2004 in a National General Hospital. Clinical records, hematoxylin & eosin-stained slides and immunohistochemical studies from 78 patients with malignant lymphoma of the skin were reviewed.Results: 67/78 cases (85,9%) were primary cutaneous lymphomas and 11/78 (14,1%) were secondary cutaneous lymphomas. Most frequent secondary cutaneous lymphoma was systemic adult T-cell lymphoma/Leukemia (ATLL), accounting for 72% of cases. Most frequently found primary cutaneous lymphoma were mycosis fungoides (MF), in 30/67 (44,7%) patients, cutaneous ATLL in 13/67 (19,4%), and non-specific peripheral T-cell lymphoma in 4/67 (6%). 5-year survival rates for MF, cutaneous ATLL and systemic ATLL were 77%, 18%, and 0%, respectively.Conclusions: MF and ATLL are the more frequently found primary cutaneous lymphomas in our hospital. MF has a good prognosis, while cutaneous ATLL has a poor survival rate.